Processing, Characterization and Disintegration Properties of Biopolymers Based on Mater-Bi® and Ellagic Acid/Chitosan Coating - Guarda-Moraga, A; Galotto-Lopez, M; Rojas-Sepulveda, A; Torres-Mediano, A; Villegas-Vallejos, C (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Among the most promising synthetic biopolymers to replace conventional plastics in numerous applications is MaterBi® (MB), a commercial biodegradable polymer based on modified starch and synthetic polymers. Actually, MB has important commercial applications as it shows interesting mechanical properties, thermal stability, processability and biodegradability. On the other hand, research has also focused on the incorporation of natural, efficient and low-cost active compounds into various materials with the aim of incorporating antimicrobial and/or antioxidant capacities into matrix polymers to extend the shelf life of foods. Among these is ellagic acid (EA), a polyphenolic compound abundant in some fruits, nuts and seeds, but also in agroforestry and industrial residues, which seems to be a promising biomolecule with interesting biological activities, including antioxidant activity, antibacterial activity and UV-barrier properties. The objective of this research is to develop a film based on commercial biopolymer Mater-Bi® (MB) EF51L, incorporating active coating from chitosan with a natural active compound (EA) at two concentrations (2.5 and 5 wt.%). The formulations obtained complete characterization and were carried out in order to evaluate whether the incorporation of the coating significantly affects thermal, mechanical, structural, water-vapor barrier and disintegration properties. From the results, FTIR analysis yielded identification, through characteristic peaks, that the type of MB used is constituted by three polymers, namely PLA, TPS and PBAT. With respect to the mechanical properties, the values of tensile modulus and tensile strength of the MB-CHI film were between 15 and 23% lower than the values obtained for the MB film. The addition of 2.5 wt.% EA to the CHI layer did not generate changes in the mechanical properties of the system, whereas a 5 wt.% increase in ellagic acid improved the mechanical properties of the CHI film through the addition of natural phenolic compounds at high concentrations. Finally, the disintegration process was mainly affected by the PBAT biopolymer, causing the material to not disintegrate within the times indicated by ISO 20200. © 2023 by the authors.